325 Immunotherapy with B cell activating antibody CPI-006 in patients (pts) with mild to moderate COVID-19 stimulates anti-SARS-CoV-2 antibody response, memory B cells and memory T effector cells. (9th November 2020) - Criner, Gerard; Mobasher, Mehrdad; Hill, Craig; Hu, Shenshen; Mahabhashyam, Suresh; Brody, Joshua; Marron, Thomas; Willingham, Stephen; Miller, Richard
Abstract : Background: CD73 is present on subsets of B and T cells and is involved in lymphocyte activation. CPI-006 is a humanized IgG1, Fcγ receptor deficient anti-CD73 that has agonistic properties. In vitro studies and ongoing cancer clinical trials show that CPI-006 binds to B cells leading to expression of CD69, trafficking to lymph nodes, immunoglobulin class switching, transformation to plasmablasts and generation of memory B cells[1]. Recently, a patient in the cancer trial with asymptomatic COVID-19 developed high titers of neutralizing anti-SARS-CoV-2 antibodies following administration of CPI-006. A phase 1 trial in COVID-19 was initiated to evaluate the use of CPI-006 to enhance anti-viral immune response (NCT04464395 ). Methods: Single intravenous dose escalation with N=5 per cohort of 0.3, 1.0, 3.0 and 5.0 mg/kg. Pt eligibility included PCR positive nasal swab for COVID-19; hospitalized with O2 saturation of ≥92% on <5 l/min of O2 . Pts received standard care for COVID-19. Pts were monitored for safety, COVID-19 symptoms, inflammatory markers and anti-SARS-CoV-2 antibodies by ELISA. Immunophenotyping of blood by flow cytometry was performed. Results: 10 pts have been treated in the first 2 cohorts; median age 64 (range 28–76) and all had comorbidities: diabetes (4), hypertension (2), obesity (7) and/or cancer (2). Median duration of symptoms prior to CPI-006 was 8 days (range 1–21 days). No treatment-related adverse events were reported. There was no correlation between duration of symptoms and baseline anti-viral titers. Kinetics of anti-SARS-CoV-2 response to spike protein are shown for 7 pts with follow-up ≥ 7 days post CPI-006 (figure 1). One pt with lymphopenia (600/mm3) had delayed response to CPI-006; all other pts generated antibody response by Day 7 post-CPI-006 to both spike and RBD. Increasing titers of IgG and IgM antibodies were observed out to 28 days post treatment. In one pt examined, memory B cells increased from 1.81% to 4.83% of B cells 28 days after treatment with serum IgG titers to spike and to RBD of >1:50, 000. 2 of 2 pts had increase in both CD4 and CD8 T effector memory cells at day 28. All pts were discharged (median 4 days) with clinical improvement. Conclusions: CPI-006 is well tolerated in COVID-19 pts. Low baseline titers of antibodies to virus were increased following CPI-006 in all treated pts. Immunomodulation with CPI-006 represents a novel therapy for COVID-19 aimed at stimulating more robust and prolonged anti-SARS-CoV-2 immunity potentially after infection or with vaccination. Trial Registration: NCT04464395 Ethics Approval: The study was approved by Temple University Hospital's Ethics Board, Western IRB, approval number 1-1317457-1. Reference: Luke J, Powderly J, Merchan J, Barve M, Hotson A, Mobasher M, Kwei L, Luciano G, Buggy J, Piccione E, Miller R. Immunobiology, preliminary safety, and efficacy of CPI-006, an anti-CD73 antibody with immune modulating activity, in a phase 1 trial in advanced cancers. J Clin Oncol 2019; 37:15 suppl, 2505.